(untitled) (International Journal of Banking and Finance, 2016)
This paper provides evidence on how stock market index reacts to releases of market-relevant information by five Middle-eastern and North African country budget and general election results. After estimating the ARMA (1, 2) estimator using daily stock returns over a recent five-year period, it was found that the market price effect over is a 20-day test window. The stock price adjustment to national annual budget announcement is significant, and the speed of adjustment is around two days to announcement. The national general election news attracts a faster adjustment time in all five countries tested. These findings of macro level market price effects from two key events are new to the literature.